Linking Millet Farmer Producer Organizations to Market through Millet Startups - Sangappa; Manjuprakash; Dholi, Rohit; Dholi, B. Laxmi; Pattanaik, Suvra (Journal of Agricultural Extension Management, 2022)
The aggregation of farmers is the need of the hour, as they are cultivating in small patches of land which is not economical to purchase inputs and market their produce. However, the green revolution has improved the production and productivity of major staple food crops of India and was successful in achieving self-sufficiency in food. Despite this, it is still observed that malnutrition, undernutrition and obesity among people, which is due to the deficiency of nutrients, vitamins and other essential components in the food system is resulting in hidden hunger. Hence, the demand for nutri-cereals or millets is increasing in the market for their nutritional value and capacity to combat lifestyle ailments. In this background, ICAR-IIMR, Hyderabad is involved in the formation and handholding of 31 Millet FPOs across four states of India to balance the demand and supply in the market. As a Cluster Based Business Organization (CBBO), IIMR is organizing capacity building programs for BoDs and CEOs of newly formed FPOs further helping them in infusing the same skills to their shareholders. It is also supporting FPOs to connect to line departments. FPOs are also millet startups, SAUs and KVKs for technical support. To transform the farmers and their organization into a business entity, IIMR has trained FPOs to undertake processing and value addition of millets and connecting to markets. An efforts was also made by IIMR to connect FPOs to e-marketing channels to sell their products directly to the intended consumers